Piano sonata no. 8 in C minor, op. 13 (Simrock) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Czerny, Carl, 1791-1857:::Contributor:::::::::::: (Germany; Bonn; N. Simrock, 2025)
Edition of the Piano Sonata no. 8 in C minor, op. 13, published after 1856 by N. Simrock in Bonn, with fingerings and metronome markings added by Carl Czerny (title page lacking).